The Role of Scholastic Philosophy in the Western Intellectual Tradition in Medieval Education - Salsa, Dela Widya; Intan Sari, Nur; Humala, Reza; Syahputra, Heru (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study discusses Scholastic Philosophy as one of the main intellectual legacies of the Middle Ages (5th to early 17th centuries) and its contribution to the philosophical tradition and the Western educational system. Scholastic Philosophy is an approach that integrates philosophical logic with theology, where major figures such as Thomas Aquinas, Anselm, and Albertus Magnus attempted to harmonize religious doctrine with rationality. Scholastic educational methods, such as disputatio (structured debate) and lectio (reading and commenting on texts), became the core of learning at major universities such as Paris, Oxford, and Bologna. In addition, the Middle Ages were also marked by the great influence of Islamic civilization which was at the peak of its intellectual glory. Muslim scholars such as Al-Farabi, Ibn Sina, and Ibn Rushd not only maintained and developed the Greek philosophical tradition but also transmitted this knowledge to Europe, which ultimately influenced Scholastic Philosophy. This study aims to explore how Scholastic Philosophy plays a role in shaping the Western intellectual tradition through education and philosophy, and its relevance in integrating faith and reason. This study shows that the educational elements in Scholasticism contribute significantly to training the ability to think logically and systematically, which is the basis of the modern intellectual tradition.